The Badlands Guardian: A Human Portrait with Feathered Headdress - Saunders, William; Haas, George; Miller, James; Morgan, Keith; Dale, Michael (Journal of Scientific Exploration, 2022)
This is an analysis of a large facial formation set within a glacial moraine along the southeast corner of Alberta, Canada, known as the Badlands Guardian. The formation is presented in one aerial and three satellite images acquired over the past 70 years by the Alberta Department of Lands & Forests and Google Earth. The images reveal a profiled portrait of a human head wearing a feathered headdress. The facial features include an eye, nose, mouth, chin, neck, and jawline. The headdress consists of a headband containing a staggered set of feather-shaped extensions. When taken together these aesthetic features create the visual impression of a left-facing portrait of an indigenous tribesman wearing a feathered headdress. A claim of intelligent design is offered and a geologist and geoscientist examine natural mechanisms that could contribute to the formation of these aesthetic features. A comparison of the iconographic tribal motifs of both North and South America is presented and a request for an extensive ground exploration and additional satellite images of this formation is encouraged.